Investigation of Horizontal Parallax Only (HPO) light field 3D display - Guo, Song (2017)
To achieve glasses-free 3D vision, light field display has been proposed and implemented for a few years, while there still exists many restrictions for such device. The most serious limit of the display is its long processing time for decomposition of input light field, as it requires computation of multiple layers to reconstruct light field at designated position. To reduce computing time while keep high image fidelity of output light field, a horizontal-only parallax method is proposed and examined in this thesis. The hardware structure, mainly backlight, has a special optical and mechanical design to support new algorithm. The input light field of new algorithm only has horizontal perspectives for efficient parallel computing. While input light field images are divided into horizontal line slices, the resultant image layer fractions are combined as full images after processing. The computation time and image quality are compared with existing works, and suggestions for further improvements are given.